Desenvolvimento da linguagem matemática em alunos do 6º ano: as quatro operações na transição escolar - Roth, Isadora (2024)
This research focuses on the mathematical language observed in a 6th-grade class of elementary school students facing the impact of transitioning from the early to later years of elementary education. This school phase presents significant challenges, with Mathematics often being a recurring area of difficulty. In light of this, the study, using a qualitative approach, investigates how mathematical language can be developed to support students experiencing the impact of this transition, fostering their ability to read, write, and interpret problem-solving situations involving the four fundamental operations. The study was conducted at Escola Estadual de Ensino Médio Rocha Vieira, located in the municipality of Dilermando de Aguiar, Rio Grande do Sul, with students navigating this shift in school dynamics. Through didactic workshops designed to strengthen mathematical language in the concepts and content of the four operations with natural numbers, the research sought to answer the following question: How can mathematical language be developed in 6th-grade elementary school students to contribute to teaching and learning the four operations during the school transition process? To achieve this objective, four workshops were planned and implemented based on the analytical categories proposed by Pimm (1997): logograms, pictograms, alphabetic symbols, and punctuation symbols. The results showed that the actions taken enhanced the development of mathematical communication, encouraged students to become more autonomous and independent, and helped them face the transition with greater confidence and motivation. Thus, it is concluded that the study fostered smoother and more enjoyable teaching and learning moments, strengthening students' resilience in addressing the challenges of developing mathematical language during the school transition.